Components of efficient distance learning course - M. M. Nazar (Academy of Cognitive and Natural Sciences, 2017)
The purpose of the research is an exposure of the productive distance learning course's components carried out in Internet on the basis of modern information-communicative technologies' application. The tasks of the research are discovery of psychological-pedagogical value of virtual educational space, analysis of basic aspects of the distance learning courses's realization in this space, research of development's and application's role of the distance learning's model of participant, re-erecting of criterion parameters' tracking's technology of changes' objective registration of participants' learning activity, and others like that. The object of research is training learning system developed on the basis of Moodle electronic platform. The subject of research is components of the productive distance learning course in Internet. The basic methods of research are an analysis of theoretical sources, forming experiment carried out in the format of the distance training course, processing of data by the methods of mathematical statistics, analysis and generalization of results. 14 base components of the productive distance learning courses found out and described in the process of research. It is rotined the proper components allow to develop and inculcate productive learning online courses in learning, psychological, educational practice. Distance learning courses have enormous psychological-pedagogical potential and there are one of facilities to convert learning and education into an active, conscious, personality, creative process.